2011
DOI: 10.1007/s10683-011-9293-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion and framing effects

Abstract: International audienceWe present a new experimental evidence of how framing affects decisions in the context of a lottery choice experiment for measuring risk aversion. We investigate framing effects by replicating the Holt and Laury's (Am. Econ. Rev. 92:1644-1655, 2002) procedure for measuring risk aversion under various frames. We first examine treatments where participants are confronted with the 10 decisions to be made either simultaneously or sequentially. The second treatment variable is the order of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 24 publications
3
40
0
1
Order By: Relevance
“…We detected a framing effect; children starting with high probabilities of gain exchanged more than children starting with low probabilities of gain. Variations in framing are known to affect significantly decisions and risk-aversion in adults [39], [40]. Individuals are risk-averse when presented with value-increasing options, but more risk-taking when faced with decreasing values [41][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We detected a framing effect; children starting with high probabilities of gain exchanged more than children starting with low probabilities of gain. Variations in framing are known to affect significantly decisions and risk-aversion in adults [39], [40]. Individuals are risk-averse when presented with value-increasing options, but more risk-taking when faced with decreasing values [41][43].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals are risk-averse when presented with value-increasing options, but more risk-taking when faced with decreasing values [41][43]. Recent studies have reported that behavioral responses to framing may vary according to the set-up used [40]. For example, high incentives to win can have more impact on risk aversion than low incentives.…”
Section: Discussionmentioning
confidence: 99%
“…17 One disadvantage is that responses appear to be susceptible to various systematic framing effects connected to the ranges and frequencies selected by the researcher and the order in which rows are presented. Parducci (1965) provides an early discussion of range-frequency effects, Levy-Garboua et al (2012) and Loomes and Pogrebna (2014a) report such effects in tables intended to elicit risk attitudes, and Sanchez Martinez et al (2015) find evidence of such effects in the context of health state evaluation. Of course, if decisions are the result of some process of sampling and accumulation, it would not be surprising to find that "cues" provided by MPLs are liable to have various systematic effects.…”
Section: Competing Explanations: Further Exploration Of the Datamentioning
confidence: 99%
“…In other experiments, Chetan Dave et al (2010) consider the effect of differing degrees of difficulty. Framing effects are reported in Mark Isaac and Duncan James (2000) and Louis Lévy-Garboua et al (2012). Our robustness test yields a different type of confound.…”
Section: Purposementioning
confidence: 70%